Career Development among Undergraduate Students of Madda Walabu University, South East Ethiopia (Journal of Student Affairs in Africa, 2021)
Career guidance and counselling is a vaguely implemented concept in most educational institutions, governmental and non-governmental organisations. The severity of the problem and scarcity of relevant information among university students have prompted the undertaking of this study the aim of whichwas to  assess career development among undergraduate students of Madda Walabu University. Crosssectional study design was employed to gather quantitative data through self-administered structured questionnaires. The participants in the study were 605 undergraduate students of Madda WalabuUniversity who were recruited through multi-stage sampling. The analysis employed SPSS-20.0 to calculate t-test and ANOVA. The findings suggested that socio-demographic variables were important in determining the factors, levels and variances in career development. The participants’ perceived benefitof career development has shown that there is a statistically significant difference between the expected mean and the observed mean, t(604) =29.11, p
Keywords: career development; socio-demographic variables; university students; Madda Walabu University; Career guidance; non-governmental organisations